2019
DOI: 10.4314/jasem.v23i3.18
|View full text |Cite
|
Sign up to set email alerts
|

Succession pattern of insects in relation to killing methods of <i>Rattus norvegicus</i> at Delta State University, Abraka, Nigeria

Abstract: The succession pattern of insects associated with the strangling and slaughtering of rat (Rattus norvegicus) was conducted between March and June 2017. Four (4) Albino Wistar rats were killed using strangle and slaughter methods, one method for a pair. The rat carcasses were secured from scavengers and restricted from human interference in a way that did not necessarily restrict access to the carcasses and also enabled insect collection. Insects were collected daily by hand picking and with the aid of aerial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
(11 reference statements)
1
0
1
Order By: Relevance
“…Abd El-bar and Sawaby (2011) agreed with our results which observed that ants were mostly found in early decomposition stages of organophosphate treated rabbit. However, reverse our results for slaughtered carrion; Ojianwuna et al (2019) recorded the appearance of ants around the slaughtered rat cadavers starting from the fresh stage to the active decay stage without a particular pattern. Consequently, we concluded that ants did not necessarily breed on the carcasses or influence the decomposition process which makes them not one of the most important forensic insects (Mabika et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Abd El-bar and Sawaby (2011) agreed with our results which observed that ants were mostly found in early decomposition stages of organophosphate treated rabbit. However, reverse our results for slaughtered carrion; Ojianwuna et al (2019) recorded the appearance of ants around the slaughtered rat cadavers starting from the fresh stage to the active decay stage without a particular pattern. Consequently, we concluded that ants did not necessarily breed on the carcasses or influence the decomposition process which makes them not one of the most important forensic insects (Mabika et al, 2014).…”
Section: Discussioncontrasting
confidence: 99%
“…Also the abundance of maggots on the slaughtered carrions was more than that on control carrions so the slaughtered corpse consumed and decayed faster. This result is in agreement with Ojianwuna et al (2019) and Farag et al (2021).…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed that five decomposition stages namely: fresh, bloated, active decay, advanced decay and dry/skeletonization were observed in both seasons irrespective of placement method. This result agrees with several researchers [35,36], except [14] on Rattus norvegicus who observed only three decomposition stages and [6] study on Sus scrofa in Delta and Akwa Ibom States in southern Nigeria, who observed four decomposition stages.…”
Section: Discussionsupporting
confidence: 92%
“…There have been trending reports of suspicious deaths of domestic animals and humans around residential areas [8], and monitoring of insects associated to decomposition has been studied in countries like Australia, USA, Canada, Argentina, Brazil [9,10] and [11,12], and more recently in Nigeria by [13] in Rivers State; [14] in Delta State; [15] in Awka, Anambra State, and [16] in Enugu State. Evidently, no studies on forensic entomology have been documented in Abia State.…”
Section: Introductionmentioning
confidence: 99%